ESTUDO DO DESEMPENHO TÉRMICO DE ARGAMASSA COM ADIÇÃO DE RESÍDUO DE POLIURETANO - Sena, Priscila L. S.; Teixeira, Carla F. B.; Labaki, Lucila C. (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
In view of the environmental crisis that threatens nature a few years ago, the study of alternatives that enable continuity of progress and human existence is necessary. Among the serious environmental problems, one can mention is the generation of residue. In order to propose a destination for polyurethane residues generated in the manufacture of surfboards, this survey realized the temperature monitoring of mortar plates with different sand substitution proportions by this residue (50%, 75% and 100%) in comparison to a reference mortar without replacement (mortar + lime + sand) subjected to an artificial heat source, comparing the phenomena of thermal exchanges occurring in each of them and consequently the thermal performance capability of the plates. From the comparison of the results obtained can be affirmed the thermal viability of all the substitution levels relative to the reference mortar (AR00), demonstrating that they can isolate the internal environment more efficiently in relation to external temperature. The AR100, mainly, demonstrated very relevant values, and can be used in extreme climates since it obtained temperature differences near 20º C between the faces.